The ecological–societal underpinnings of Everglades restoration. Issue 3 (1st April 2005) - Sklar, Fred H.; Chimney, Michael J.; Newman, Susan; McCormick, Paul; Gawlik, Dale; Miao, ShiLi; McVoy, Christopher; Said, Winifred; Newman, Jana; Coronado, Carlos; Crozier, Gaea; Korvela, Michael; et al.
Abstract : The biotic integrity of the Florida Everglades, a wetland of immense international importance, is threatened as a result of decades of human manipulation for drainage and development. Past management of the system only exacerbated the problems associated with nutrient enrichment and disruption of regional hydrology. The Comprehensive Everglades Restoration Plan (CERP) now being implemented by Federal and State governments is an attempt to strike a balance between the needs of the environment with the complex management of water and the seemingly unbridled economic growth of southern Florida. CERP is expected to reverse negative environmental trends by "getting the water right", but successful Everglades restoration will require both geochemical and hydrologic intervention on a massive scale. This will produce ecological trade‐offs and will require new and innovative scientific measures to (1) reduce total phosphorus concentrations within the remaining marsh to 10 µg/L or lower; (2) quantify and link ecological benefits to the restoration of depths, hydroperiods, and flow velocities; and (3) compensate for ecological, economic, and hydrologic uncertainties in the CERP through adaptive management.